2011
DOI: 10.1186/1476-511x-10-71
|View full text |Cite
|
Sign up to set email alerts
|

Fish oil consumption prevents glucose intolerance and hypercorticosteronemy in footshock-stressed rats

Abstract: BackgroundEnvironmental stress plays an important role in the development of glucose intolerance influencing lipid and glucose metabolism through sympathetic nervous system, cytokines and hormones such as glucocorticoids, catecholamines and glucagon. Otherwise, fish oil prevents glucose intolerance and insulin resistance. Although the mechanisms involved are not fully understood, it is known that sympathetic and HPA responses are blunted and catecholamines and glucocorticoids concentrations can be modulated by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 41 publications
1
4
0
Order By: Relevance
“…Regarding the endocrine pancreatic function, serum biochemical analysis revealed that chronic stress produced a significant increase in the serum insulin and glucose levels, with increasing insulin resistance reflected by increasing HOMA-IR index. These results come in line with previous studies (Eguchi et al 2011;Rafacho et al 2010;Zardooz et al 2012) that reported that stress affects the endocrine pancreas and can lead to the production of diabetes mellitus by different mechanisms.…”
Section: Discussionsupporting
confidence: 93%
“…Regarding the endocrine pancreatic function, serum biochemical analysis revealed that chronic stress produced a significant increase in the serum insulin and glucose levels, with increasing insulin resistance reflected by increasing HOMA-IR index. These results come in line with previous studies (Eguchi et al 2011;Rafacho et al 2010;Zardooz et al 2012) that reported that stress affects the endocrine pancreas and can lead to the production of diabetes mellitus by different mechanisms.…”
Section: Discussionsupporting
confidence: 93%
“…In this study, the blood glucose levels of animals submitted to stress were increased. This result was due to activation of the hypothalamic‐pituitary‐adrenal axis and the sympathetic nervous system, which results in increased production of catecholamines and glucocorticoids, respectively, with a consequent increase in glucose production by the liver and decreased use by tissues 40 . With respect to insulin levels, in the present study the authors chose to quantify them indirectly, through the measurement of plasma C‐peptide.…”
Section: Discussionmentioning
confidence: 99%
“…Reduced ω-3 fatty acid levels have previously been associated with glucose intolerance and insulin resistance (Abbott et al, 2016; Eguchi et al, 2011; Flachs et al, 2014; Lamping et al, 2013; Lepretti et al, 2018; O’Mahoney et al, 2018; Ramel et al, 2008). We therefore hypothesized that overcoming the deficit in DHA levels might prevent the adverse physiological effects that we observed in statin-treated female mice.…”
Section: Resultsmentioning
confidence: 99%